The relationship between coping strategies and quality of life of patients with lung cancer - ERBAY, Ercüment; ASLAN, Harun; BOLGUN, Cemre (Hatay Mustafa Kemal University Faculty of Medicine, 2022)
Objective: In this study, it is aimed to examine the coping strategies and quality of life of patients with lung cancer. In this context, the relationship between strategies for coping with lung cancer and the quality of life of patients is discussed. The effect of treatment duration on coping strategies and quality of life is also being examined. Method: The cross-sectional survey study and the convenience sampling method were used in the study. The World Health Organization Quality of Life- BREF (WHOQOL-Bref; 27 items) and Coping Orientation to Problems Experienced Inventory (Brief-COPE; 28 items) were used as scales. The data of this research were obtained from 201 patients diagnosed with lung cancer and undergoing treatment. Results: Research results show that 53.0% of the participants were women and 86.1% were married. In addition, the mean age of the participants was 57.19±7.01 (mean ± s. Deviation). A positive correlation emerged between each domain of the WHOQOL-BREF scale. As for the coping scale, it was determined that there were positive and weak relationships between problem-focused coping strategies and quality of life in active coping, planning and positive refraining strategies. It was determined that there was a positive and weak relationship between positive emotion-focused coping strategies and quality of life in all coping strategies. Finally, it was determined that negative emotion-focused coping strategies such as ventilation, behavioral disengagement, denial, and self-blame were affecting the patient’s quality of life negatively. Conclusion: In conclusion, lung cancer patients who used both problem-focused and positive emotion-oriented coping strategies achieved a higher quality of life. On the other hand, it is an important conclusion to consider that negative emotion focused coping strategies negatively affect patients’ quality of life. Finally, it can be expressed as another conclusion of this study that age, income and duration of treatment affect both the quality of life and coping strategies of lung cancer patients.
Keywords: Yaşam kalitesi; baş etme stratejileri; akciğer kanseri; tedavi süresi; Health Care Administration; Sağlık Kurumları Yönetimi; Quality of life; coping strategies; lung cancer; duration of treatment; 16. Peace & justice; 3. Good health